Cultural power dynamics and narrative transformation: a comparative analysis of Hollywood film remakes in contemporary Asian cinema - Sonni, Alem Febri; Irwanto, Irwanto; Hafied, Hasdiyanto; Putri, Vinanda Cinta Cendekia (Frontiers in Communication, 2025)
This study examines the complex dynamics of cultural adaptation in Asian remakes of Hollywood films, focusing on two pairs of films produced between 2015 and 2023. Through systematic intertextual and comparative analysis, the research investigates how Asian film remakes negotiate and transform global narratives within local cultural contexts. The study analyzes “Ghost” (1990) and its Japanese remake “Ghost: In Your Arms Again” (2018), and “Miss Congeniality” (2000) and its Chinese remake “Beauty Queen” (2021). The analysis reveals sophisticated patterns of cultural transformation across multiple dimensions, including narrative structure, character relationships, visual aesthetics, and thematic emphasis. The findings demonstrate that Asian remakes employ complex strategies of cultural recalibration, moving beyond simple translation to create culturally resonant narratives that balance global appeal with local cultural values. The research identifies systematic patterns in negotiating power dynamics, particularly in treating authority, gender relations, and social hierarchies. Technical analysis reveals consistent shifts in cinematographic approaches, with Asian remakes favoring more contemplative visual styles that integrate traditional aesthetic principles. The study contributes to our understanding of contemporary global media flows and cultural power dynamics, suggesting that successful film adaptations engage in sophisticated processes of cultural hybridization that actively reshape rather than merely reproduce global narratives. These findings significantly impact understanding of cultural adaptation in an increasingly interconnected global media landscape.